Water Quality, Sanitation, and WASH Service-Level Assessment in Three Islamic Boarding Schools (Dayah) in Aceh: A Multi-Site Comparative Study - Ashari, Teuku Muhammad; Rohendi, Aulia; Faridy, Faizatul; Rahman, Arief; Dipa, Syahrul Ridha; Effendi, Rijal; Tanjung, Aris Muda; Athaya, Ahmad Faiq; Maulana, Teuku Rian (Journal of Community Based Environmental Engineering and Management, 2026)
This study compared drinking-water quality, general-use water quality, sanitation conditions, and water, sanitation, and hygiene (WASH) service levels in three Islamic boarding schools (dayah) in Aceh Province, Indonesia. An exploratory multi-site mixed-methods design combined six point-of-use water samples, site observation, management interviews, and questionnaires administered to 10 students at each site. Water quality was assessed using pH, turbidity, total dissolved solids (TDS), and H₂S screening at all sites, while culture-based Escherichia coli and Total Coliform testing was conducted at only one site because of laboratory capacity constraints. Service performance was evaluated using an adapted WASHCost framework covering quality, quantity, accessibility, and reliability. Drinking water generally met the study reference ranges for pH and turbidity, but TDS exceeded the operational threshold of 300 mg/L at Al-Muslimun (400 mg/L) and Darul Aman (548 mg/L). General-use water showed the clearest cross-site weakness: H₂S screening was positive at 24 and 72 hours at all three dayah. Darul Aman recorded high turbidity (6.59 NTU) and TDS (1,051 mg/L), and Al-Muslimun showed a Total Coliform Count of 151 CFU/100 mL in general-use water, with E. coli non-detectable. Student perceptions were generally positive, indicating a perception-risk gap. Under the adapted WASHCost assessment, Al-Muslimun and Darul Ulum were classified as intermediate, whereas Darul Aman was classified as substandard. These findings suggest that dayah WASH improvement should prioritize the protection and routine monitoring of general-use water systems, not only treated drinking-water points.